Analisis Pengaruh Kesadaran dan Persepsi serta Preferensi Konsumen terhadap Pola Konsumsi Buah Lokal (Studi pada Konsumen di Pasar Cileungsi Kabupaten Bogor) - Stefani Septi Anggraeni; Kuswarini Sulandjari; Slamet Abadi (Jurnal Ilmiah Wahana Pendidikan, 2022)
There are quite a number and types of fruit produced in the territory of Indonesia, so that the availability in the local market is abundant during the harvest season. Non-local fruits are also circulating in the market, including at Pasar Cileungsi, Bogor. The quality of non-local fruit is quite high. To maintain market absorption of local fruit, it is necessary to prevent a shift in consumption patterns of local fruit to non-local fruit. The purpose of this study was to describe consumer awareness, perception, and preferences of local fruit and to analyze their effect on local fruit consumption patterns simultaneously and partially. This study uses primary data and secondary data. Primary data was taken by interview technique using a questionnaire. accidental sampling, a number of 100 fruit consumers. Secondary data were obtained from the relevant agencies in this study, namely data from BPS and literature studies. The analysis technique used: Likert scale, score, descriptive, correlation, and multiple linear regression. The results of the study: Awareness and consumer preferences for local fruit are at a strong level; Consumer perceptions of local fruit at a very strong level; Consumer preferences for local fruit types in order are: melon, pineapple, Medan orange, Malang apple, salak pondoh; Consumer consumption patterns for local fruit are at a strong level; Simultaneously the variables of awareness, perception, preference have a significant effect on local fruit consumption patterns at the alpha level of 5%; Awareness has a significant effect with a positive coefficient on local fruit consumption patterns (at 5% alpha level); Perceptions and preferences have no significant effect with the direction of the positive coefficient on local fruit consumption patterns (at 5% alpha level).